2020
DOI: 10.1186/s12887-020-1971-z
|View full text |Cite
|
Sign up to set email alerts
|

Distribution characteristics of cow’s milk-sIgE components in children with respiratory allergic diseases in southern China

Abstract: Background: Cow's milk (CM) is the main food allergen for toddlers and infants. Presently, studies on CM specific immunoglobulin E (sIgE) sensitization and positive distribution of CM components ALA-, CAS-, and BLG-sIgE are lacking in infants with respiratory allergic diseases, especially in southern China. This study therefore aimed to investigate the distribution of CM sensitization and the relation between its components α-lactalbumin (ALA), β-lactoglobulin (BLG) and casein (CAS) sIgE in children with respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In the last ten years several studies have been performed to identify relevant allergen sources in the Chinese area. We have summarized in Table 2 studies performed by skin testing with allergen extracts, IgE serology using allergen extracts or by questionnaires (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). Table 2 indicates the regions where the studies had been performed, the climate prevailing in the region, what subjects (e.g., general population, patients with allergic symptoms, etc.)…”
Section: Frequencies Of Allergic Sensitizations To Allergen Sources In China: First Information From Allergen Extract-based Studiesmentioning
confidence: 99%
“…In the last ten years several studies have been performed to identify relevant allergen sources in the Chinese area. We have summarized in Table 2 studies performed by skin testing with allergen extracts, IgE serology using allergen extracts or by questionnaires (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). Table 2 indicates the regions where the studies had been performed, the climate prevailing in the region, what subjects (e.g., general population, patients with allergic symptoms, etc.)…”
Section: Frequencies Of Allergic Sensitizations To Allergen Sources In China: First Information From Allergen Extract-based Studiesmentioning
confidence: 99%
“…Interestingly, > 38% of patients are polysensitized, and majority of patients were co-sensitized to both D. farina and D. pteronyssinus; C. pagurus , P. monodon , and B. germanica ; or milk and egg whites. In previous studies, we reported an extensive cross-reaction between D. farina and D. pteronyssinus 11 ; C. pagurus , P. monodon , and B. germanica 12 ; milk and egg whites 10 , 13 . Thus, we can test positive for one of the above allergens and then easily deduce that the patient is also positive for the others 14 , 15 .…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, A. alternata was also one of the five main allergens in children aged < 14 years. This may be attributed to different lifestyle and physiological conditions of people with different age 10 . Therefore, age is an important factor to consider when establishing or selecting the panel of allergen detection.…”
Section: Discussionmentioning
confidence: 99%